2013
DOI: 10.1016/j.pain.2013.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen status and psychophysical stress modify temporomandibular joint input to medullary dorsal horn neurons in a lamina-specific manner in female rats

Abstract: Estrogen status and psychological stress contribute to the expression of several chronic pain conditions including temporomandibular muscle and joint disorders (TMJD). Sensory neurons that supply the temporomandibular joint (TMJ) region terminate in laminae I and V of the spinal trigeminal nucleus (Vc/C1-2 region); however, little is known about lamina specificity and environmental influences on the encoding properties of TMJ brainstem neurons. To test the hypothesis that Vc/C1-2 neurons integrate both interoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 72 publications
5
30
0
Order By: Relevance
“…This same subchronic stress paradigm induced somatic thermal and chemical hypersensitivity that lasted approximately 8 days and sensitized trigeminal nucleus caudalis neurons to noxious stimulation of the temporomandibular joint 47,50,51 . The unique aspect of our model is that requisite muscle injury prior to stress transitioned the stress-induced visceral hypersensitivity from acute or transient to chronic pain, persisting at least 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This same subchronic stress paradigm induced somatic thermal and chemical hypersensitivity that lasted approximately 8 days and sensitized trigeminal nucleus caudalis neurons to noxious stimulation of the temporomandibular joint 47,50,51 . The unique aspect of our model is that requisite muscle injury prior to stress transitioned the stress-induced visceral hypersensitivity from acute or transient to chronic pain, persisting at least 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, currently available animal models of pain arising from the viscera or the temporomandibular joint fluctuate across the estrous cycle and are sensitive to hormonal manipulation 3,9,18,31,33,37,41,47,53 . Estrogen is pronociceptive in many visceral pain models in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Since chronic pain and learning and memory likely share common pathways (Ji et al, 2003) and that estrogen status influences TMJ nociceptive processing (Bereiter and Okamoto, 2011), we sought to determine if group I antagonists had a differential effect on TMJ nociceptive processing under high and low estrogen conditions. Previously, we reported that the encoding properties of TMJ-responsive neurons in superficial laminae at the Vc/C 1-2 region varied over the estrous cycle in intact female rats (Okamoto et al, 2003), and matched well the results seen following high-vs. low-dose exogenous E2 treatment (Tashiro et al, 2007;Okamoto et al, 2013). Thus, it was unexpected to find that E2 status did not have a greater influence on the effectiveness of group I antagonists to inhibit TMJ nociception, although lesser effects were noted.…”
Section: Discussionmentioning
confidence: 96%
“…Previously, we determined that the response properties of TMJ neurons in the superficial laminae at the Vc/C 1-2 region varied over different stages of the estrous cycle in intact female rats (Okamoto et al, 2003). Furthermore, systemic administration of estradiol (E2) for 2 days (Tashiro et al, 2007;Okamoto et al, 2013) or acute local application (Tashiro et al, 2012) significantly altered TMJ-evoked activity of Vc/C 1-2 neurons in ovariectomized (OvX) female rats in a dose-related manner.…”
Section: Introductionmentioning
confidence: 99%
“…The central projections of sensory nerves that supply the TMJ region terminate mainly in the trigeminal subnucleus caudalis (Vc)/upper cervical cord (Vc/C 1–2 ) region (Jacquin et al, 1983, Takemura et al, 1987, Shigenaga et al, 1988). Previously, we reported that estrogen status (Okamoto et al, 2003, Tashiro et al, 2007) and psychophysical stress influenced the encoding properties of TMJ-responsive neurons at Vc/C 1–2 region in a lamina-specific manner (Okamoto et al, 2012, Okamoto et al, 2013). Female gender and psychological distress are risk factors for persistent TMJ pain (LeResche, 1997, Bereiter and Okamoto, 2011, Maixner et al, 2011, Slade et al, 2014).…”
Section: Introductionmentioning
confidence: 99%